We have to solve for x given that : x^(-4/3)-1=15

x^(-4/3) - 1 = 15

=> x^(-4/3) = 15 + 1

=> x^( -4/3) = 16

Take the log to base 4 of both the sides

=> log [ x^(-4/3)] = log 4^2

=> - 4/3 log x = 2

...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to solve for x given that : x^(-4/3)-1=15

x^(-4/3) - 1 = 15

=> x^(-4/3) = 15 + 1

=> x^( -4/3) = 16

Take the log to base 4 of both the sides

=> log [ x^(-4/3)] = log 4^2

=> - 4/3 log x = 2

=> log x = -2*3/4

=> log x = -3/2

As the base of the log is 4

=> x = 4^(-3/2)

=> x = 2^(-3)

=> x = 1/8

**Therefore the required value of x is 1/8.**